Optimizing Shallot Growth through Variations Fertilization NPK and Plant Density - Alfonso Sitorus; Erpina Delina Manurung (Journal of Global Innovations in Agricultural Sciences)
Variations in macronutrient fertilization and spacing are two important components in increasing shallot yield. This study aims to determine the effect of fertilization and plant spacing on shallot yield. A split-plot design with three replications was applied. The main plots were plant spacing (D1: 20 x 20 cm, D2: 20 x 15 cm, D3: 20 x 10 cm); subplots were fertilization of TSP, NPK, KNO3, Urea, and ZA with four doses: F1 by 188, 600, 0, 180, 400 kg ha-1; F2 by 75, 225, 80, 57, 300 kg ha-1; F3 by 100, 300, 107, 76, 400 kg ha-1; and F4 by 125, 375, 135, 95, 500 kg ha-1, respectively. Data was analyzed using the Anova (Analysis of Varians) and Duncan tests. The number of leaves was positively correlated with wet bulb weight per clump (R2 = 86.36%), and dry bulb weight per clump (R2 = 72.40%). The optimum N, P, and K dosages to achieve the optimum relative yield were 126.85; 178.06; 95.25 kg ha-1. The D3F3 interaction (plant spacing of 20x10 cm with TSP, NPK, KNO3, Urea, and ZA fertilization by 100, 300, 107, 76, and 400 kg ha-1, respectively) enhanced the dry bulbs weight per plot by 84.50%.